Analisis perhitungan Hi per Mil (H-1000) sebagai dasar pembagian keuntungan nisbah bagi hasil produk deposito - Rohman, Nyco Dhana (Maliki Interdisciplinary Journal, 2024)
The economic crisis that occurred in Indonesia was one of the phenomena that was enough to disrupt the wheels of the banking business. Islamic banking was strong enough to survive in the economic crisis. The aim of this research is to find out the factors that influence the resilience of Islamic Banking in facing the economic crisis. This type of research is descriptive qualitatieve, with the method of observation, interviews, and documentation. The results and discussion show that H-1000 is one of the factors that influence the resilience of Islamic Banking, because Islamic Banks use the principle of revenue sharing on iB Hijrah deposit products which are presented in the form of ratios, and are calculated on the basis of H-1000 or banking profits in managing in customer funds